Liquefaction during the Kumamoto Earthquakes on April 14 and 16, 2016 - K. Wakamatsu; S. Senna; K. Ozawa (International Association of Lowland Technology, 2017)
At 21:26 JST on April 14, 2016, an earthquake with a Japan Metrological Agency Magnitude (MJMA) of 6.5 struck Kumamoto Prefecture, Kyushu, in southwestern Japan. This earthquake was followed by a larger earthquake with an MJMA of 7.3 at 1:25 JST on April 16, 2016. These were the most severe earthquakes to occur in Japan since the Tohoku earthquake in 2011. The hypocenters of the strike-slip MJMA 6.5 foreshock and MJMA 7.3 main shock and, along with the aftershocks, were widely distributed along the active Futagawa-Hinagu strike-slip fault. This paper first presents the distribution of the liquefied sites during these earthquakes and their effects on the surrounding buildings and infrastructure. Next, the distance from the epicenter to the farthest liquefied site is compared with past Japanese earthquakes, followed by a discussion on the intensities of the ground motion that caused the liquefaction. Finally, the land conditions and soil profiles where severe and widespread liquefaction occurred are investigated.